Curing Characteristics and Quality Evaluation of Turmeric Finger - Sharma, P D; Sinha, Mohan Kumar; Kumar, Vinay (Journal of Agricultural Engineering, 2008)
The curing characteristics of turmeric (Deshla variety) were evaluated at varying curing temperature (80, 90 and 100degree C), water turmeric finger ratio (0.75:1, 1:1 and 1.251:1) and different curing times (10, 20, 30, 40, 50 and 60 min). The optimum curing time was found to be 40 min based on the final moisture content and hardness. Moisture content and hardness of turmeric fingers after 40 min were found to be 76.21% (w.b) and 3.4 kg force, respectively. Some important physical and sensory evaluations were also carried out to test the quality of raw as well as processed turmeric. The laboratory processed turmeric fingers samples were also compared with traditionally as well as market samples. The traditionally processed samples were found inferior in all the quality attributes viz. colour, flavor, appearance and overall acceptability whereas the laboratory processed samples were at par with the market samples.